Synthesis and Reactivity of Mixed Dimethylalkynylaluminum Reagents - Piccardi, Riccardo; Turcaud, Serge; Benedetti, Erica; Micouin, Laurent (Synthesis, 2019)
Organoaluminum derivatives are mostly appreciated for their Lewis acidity properties, but generally not considered as reagents of choice in synthetic transformations involving the creation of C–C bonds. Among these species, dimethylalkynylaluminum reagents represent a special class of compounds, with, in many cases, unique reactivity. This review summarizes the preparation and reactivity of these organometallic reagents with a focus on their synthetic potential.1 Introduction2 Preparation of Dimethylalkynylaluminum Reagents3 Reactivity of Dimethylalkynylaluminum Reagents3.1 Reactions with Csp3 Electrophiles3.2 Reactions with Csp2 Electrophiles4 Transition-Metal-Catalyzed Reactions4.1 Addition to α,β-Unsaturated Enones4.2 Coupling Reactions5 Triple Bond Reactivity6 Conclusion
Keywords: organometallics; alkynes; organoaluminum reagents; alkynylation; metalation